Da’wa Gus Baha in the Perspective of Face Negotiation Theory : Dakwah Gus Baha dalam Perspektif Teori Negosiasi Wajah - Muhammad, Danii Syauqi; Abadi, Totok Wahyu (Universitas Muhammadiyah Sidoarjo, 2024)
Da’wa activities are currently increasingly easier to carry out due to the sophistication of existing technology. Even though the dissemination of da'wah becomes easier, the possibility of slander arising from the da'wah being delivered also increases. Therefore, preaching today is filled with challenges and sincerity. The appearance of facial negotiations when facing a da'wah problem is a very important thing to pay attention to. Because that way we can see the preacher's way of dealing with conflict. This research uses descriptive qualitative methods with content analysis techniques. The data collection techniques used were observation, documentation study, and literature study. The subject of this research is Gus Baha and the object of this research is the video content of criticism made by Faizal Assegaf as well as the video content of Gus Baha's response to this criticism. The results of this research show that Gus Baha displays a fairly calm, scientific and relaxed facial negotiation in responding to Faizal's criticism. Even though there is a lot of criticism aimed at Gus Baha, Gus Baha will not pay attention to it as long as the criticism is just empty talk. When criticized, Gus Baha tends to show a calm and scientific face.